INCREASING THE EFFICIENCY OF THE TRANSPORT TERMINAL SYSTEM IN THE REPUBLIC OF UZBEKISTAN - Qosimov, Sunnat (Science technology&Digital finance, 2024)
This article analyzes the problems of organizing international cargo transportation. It is noted that the economic indicators of the transport terminal system in international cargo transportation depend on the following indicators: the level of use of modern methods of organizing and planning rolling stock, as well as the growth rate of indicators of motor transport enterprises, the lack of a market for transport forwarding and customs warehouse services, in connection with this terminal business in all countries of the world is a large process of integration into logistics companies and transport and distribution centers.